193k views
0 votes
Solve y = x + 6 for x.

x = y + 6
x = −y + 6
x = y − 6
x = −y − 6

User Red Twoon
by
6.1k points

2 Answers

3 votes
x = y - 6 because all you have to do is move the 6 to the same side as y, which makes it negative
User JonathonW
by
5.4k points
7 votes

Answer:

The correct option is C) x = y − 6.

Explanation:

Consider the provided equation.


y = x + 6

We need to solve the provided equation for x.

Subtract 6 from both the sides.


y-6 = x + 6-6


y-6 = x


x=y-6

Thus, the value of the equation for x is
x=y-6.

Hence, the correct option is C) x = y − 6.

User Souvickcse
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.